Pedagogical monitoring and correction of the physical condition of female university students in sports-applied fitness-boxing classes - Rakovetsky, A.I.; Sycheva, I.A.; Eremeeva, N.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate and develop test exercises for the monitoring and correction of the preparedness of female university students in sports-applied fitness-boxing classes. Methods and structure of the study. The scientific work was conducted on the educational base of the Russian State Agrarian University – Moscow Timiryazev Agricultural Academy. More than 700 first- and second-year female students and 35 specialists, coaches, and teachers of physical culture and sports took part in the experiment. At the preliminary stage, testing of the preparedness of the participants of the experiment was carried out, as well as a survey of coaches and teachers on the subject of which test exercises are the most effective for the monitoring and correction of the preparedness of female students in sports-applied fitness-boxing classes. Thus, all this contributed to the accumulation of factual material and the formation of blocks of test exercises for monitoring the preparedness of female university students in sports-applied fitness-boxing classes. Results and conclusions. Based on the results of the conducted work, the following blocks of test exercises were developed and formed for monitoring the preparedness of female university students for sports-applied fitness-boxing classes: – Control exercises for general physical preparedness (GPP): running 1000 m and 60 m; standing long jump; raising the torso from a lying position for one minute; forward bend from a sitting position on the floor; flexion and extension of the arms from a support-lying position on the floor. – Control exercises for special physical preparedness (SPP): jumping on two legs with a skipping rope for one minute (number of jumps); straight punches in a boxer’s stance on the bag for one minute (number of times); from a standing position in a boxer’s stance, alternating lunges for one minute (number of lunges). – Technical preparedness (TP): imitation of simple technical actions from boxing (shadow boxing); various striking technical actions with the boxing bag. The developed control exercises make it possible to effectively manage the preparation of female university students in sports-applied fitness-boxing classes.